Investigation on the effects of oblique rotating ion implantation (ORI) for nanoscale vertical double gate NMOSFET - Razali Ismail, 1960-, author; Ismail Saad, 1974-, author; Vijay Kumar Arora, author; Regional Conference on Solid State Science and Technology (23rd : 2007 : Johor Bahru) (Skudai : Universiti Teknologi Malaysia, 2007)
PRZSL